Effect of Dysphagia on Hospital Outcomes and Readmissions in Patients with Human Immunodeficiency Virus. Issue 11 (November 2021) - Nustas, Rosemary; Dalsania, Raj; Brown, Jason; Patnana, Srikrishna V.; Qayed, Emad
Abstract : Objectives: Dysphagia is a common symptom in patients hospitalized with human immunodeficiency virus (HIV). There are limited data on the relation between dysphagia and important hospital outcomes. The aim of our study was to assess the impact of dysphagia on hospital costs, length of stay (LOS), mortality, and 30-day readmission rates in HIV patients hospitalized with dysphagia. Methods: We used the Nationwide Readmissions Database to identify all adult hospitalizations with HIV between January 2010 and September 2015. We stratified cases according to the presence of dysphagia ( International Classification of Diseases, Ninth Revision, Clinical Modification code 787.2) as a primary or secondary diagnosis, and compared clinical and hospital characteristics between the two groups. Multivariable regression models were used to compare LOS, total hospital costs, in-hospital mortality, 30-day mortality, and 30-day readmission rates between the two groups. Results: A total of 206, 332 hospitalized patients with HIV were included in the study. Of these, 8699 (4.2%) patients had dysphagia. Patients with dysphagia were more likely to have Candida esophagitis (26.8% vs 3.6%), esophageal strictures (3.1% vs 0.2%), and malnutrition (41.6% vs 17.6%); and they were more likely to undergo upper endoscopy (23.2% vs 3.8%) and percutaneous feeding tube placement (9.2% vs 0.7%), all P < 0.0001. On multivariate analysis, dysphagia was associated with longer LOS (12 vs 7.4 days; P < 0.0001), higher hospitalization cost ($32, 993 vs $21, 813, P < 0.0001), and increased 30-day readmissions (24% vs 20.8%, adjusted odds ratio 1.19; 95% confidence interval 1.12–1.25; P < 0.0001). Patients with dysphagia had higher in-hospital mortality (4.7% vs 3.5%) but this did not reach statistical significance (adjusted odds ratio 1.01; 95% confidence interval 0.91–1.12; P = 0.86). Conclusion: In hospitalized patients with HIV, dysphagia is a significant independent predictor of longer LOS, higher costs, and higher rates of 30-day readmissions. These findings highlight the importance of optimizing treatment of dysphagia in patients with HIV to mitigate its negative impact on patient and hospital outcomes. Abstract : Dysphagia is a common symptom in patients with human immunodeficiency syndrome (HIV). This study evaluates the effect of dysphagia in hospitalized patients with HIV on important hospital outcomes. Using the National Readmission Database, we identified hospitalizations in patients with HIV and stratified cases according to the presence or absence of dysphagia. We used multivariable models to compare length of stay, hospital costs, mortality, and readmission rates between the two groups.